Effect Of Public Accountability, Clarity TargetsBudget And Control System Of ManagementSkpd Managerial Performance In The District Sukoharjo - Sari, Metha Kurnia, Dr.Erma Setyawati, Ak.,MM (2016)
This study aims to determine the effect of public accountability, budget goal clarity and management control systems on managerial performance SKPD. The theory used this research is the theory of the agency is to examine the relationship SKPD leadership with subordinates. Research was conducted on all SKPD in Sukoharjo district, which includes offices, offices and agencies. The study design used in this research is quantitative research. Sampling was done by purposive sampling technique, with a total of respondents who used as many as 66 respondents. Data used in the study are primary data. Methods of data collection using questionnaires. Data were analyzed using multiple linear regression analysis with SPSS. The results of this study demonstrate public accountability positive significant effect on managerial performance SKPD Sukoharjo, proved of value thitung 4.745> t table (1,999) with a probability value of 0.000. Budget goal clarity significantly influence managerial performance SKPD Sukoharjo, proved of value thitung 5.388> t table (1,999) with a probability value of 0.000. Management control system has a significant positive effect on the managerial performance SKPD Sukoharjo, proved of value thitung 4,559> t table (1,999) with a probability value of 0.000.